Media Sosial dan Radikalisme: Bagaimana Teknologi Informasi Mempengaruhi Pemikiran Ekstrem - Aminudin, Cecep; Nugroho, Prastyawan; Sutrisno, Andri (PT Elaborium Elevasi Indonesia, 2023)
In the era of globalization driven by advances in information technology, global society is experiencing a shift from traditional lifestyles to more contemporary lifestyles. Technology, such as television, cell phones, and the internet, has influenced every aspect of our lives, including the way we communicate, work, and interact. Apart from the positive benefits it provides, information technology also brings new challenges, one of which is the spread of radical ideology through social media. In this context, radicalism, which tends to desire total and revolutionary change through extreme action, finds a fertile home on digital platforms. This research uses a qualitative approach by prioritizing a literature study and document analysis. Data was collected from various academic sources relevant to the topic of radicalism in social media, including journal articles, books, research reports, and other publications. In addition, document analysis involves collecting secondary data from various sources, such as security reports, media news, and government publications related to the spread of radicalism through social media. The research results show an increase in the prevalence of radical content on social media by 37% in the last two years. Social media, while providing communication benefits, is also an effective platform for the spread of radical ideology. “Echo chambers” on these platforms amplify individuals' extreme beliefs. Governments and other entities struggle to limit the spread of radical ideologies on digital platforms. Public awareness and education are the keys to overcoming the spread of this extreme ideology.